2020
DOI: 10.1186/s12886-020-01732-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors for childhood strabismus in Lhasa, Tibet, China: a cross-sectional, school-based study

Abstract: Background To estimate the prevalence of strabismus and associated risk factors among grade one school children in Lhasa, Tibet, China. Methods The Lhasa Childhood Eye Study (LCES) was a cross-sectional, school-based childhood study conducted in Grade one students from primary schools in Lhasa, Tibet, China. Comprehensive ophthalmic examinations and basic systemic examinations were evaluated. A questionnaire survey containing information about chil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Once the compensation range of motor fusion is exceeded, obvious eye position deviation will appear, which will damage binocular visual function. The longer the course of the disease, the greater the hindrance to stereoscopic vision development, which is not conducive to postoperative recovery [ 25 , 26 ]. Human stereoscopic vision mainly appears in 3-4 months after birth and develops basically maturely at the age of 3-4.…”
Section: Discussionmentioning
confidence: 99%
“…Once the compensation range of motor fusion is exceeded, obvious eye position deviation will appear, which will damage binocular visual function. The longer the course of the disease, the greater the hindrance to stereoscopic vision development, which is not conducive to postoperative recovery [ 25 , 26 ]. Human stereoscopic vision mainly appears in 3-4 months after birth and develops basically maturely at the age of 3-4.…”
Section: Discussionmentioning
confidence: 99%
“…Kobashi et al 5 reported that there is a small amount of riboflavin in the human corneal stroma, and the ex vivo corneal stiffness significantly increases after VL (375 nm wavelength) irradiation based on physiological riboflavin. Epidemiological data show that the prevalence of keratoconus, pterygium, dry eye disease, cataract and strabismus is significantly higher in the highlands than in the lowlands2 6–9 and the cornea of the highlanders is thinner than that of the lowlanders 10 11. Our previous study also found that the prevalence of myopia among children and adolescents in Tibet was lower than that in the plains 12.…”
Section: Introductionmentioning
confidence: 51%
“…In a cross-sectional study involving 1856 grade 1 students from primary schools, He et al found that BMI was not a risk factor for strabismus using multiple logistic regression [41]. The first possibility is that, as participants had a mean (SD) BMI of 15.74 (1.80), fewer individuals may have had both extremes of BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The first possibility is that, as participants had a mean (SD) BMI of 15.74 (1.80), fewer individuals may have had both extremes of BMI. The second possibility is that BMI could be less influential on strabismic [13] than on non-strabismic binocular vision anomalies [14], as they tested the effect of BMI in children with strabismus [41], whereas our participants had no manifest deviation for distance or near. The third possibility is that this outcome might be due to the difference in the age of participants between both studies, as He et al [41] included children with a mean (SD) age of 6.83 (0.46), who were younger than our participants (age range: 19 -25 years), as disparity in binocular vision parameters might be seen even between normal children and adults [42].…”
Section: Discussionmentioning
confidence: 99%